Electricity 1 - Kubala, Thomas ([S.l.] : Delmar Cengage Learning, 2012)
Designed to help you learn fundamental electrical concepts and explore their practical applications, this trusted book provides a thorough introduction to various types of alternating current (AC) circuits, as well as key principles such as power, power factor, power factor correction, inductive reactance, capacitive reactance, and impedance. ELECTRICITY 2: DEVICES, CIRCUITS AND MATERIALS, Tenth Edition, maintains the user-friendly style and proven approach while incorporating new material and updates based on the 2011 National Electrical Code. Featuring current industry terminology, photographs of commonly used electrical equipment, and sample problems with solutions, this convenient, affordable book is an ideal choice for anyone interested in mastering basic electricity, including AC power, wiring installation, lighting, and effective troubleshooting.